Effect of feeding wheat and rice straw based complete feed blocks on nutrients utilization, blood biochemical and growth performance in crossbred calves - SINGH, PANKAJ KUMAR; CHANDRAMONI, CHANDRAMONI; KUMAR, KAUSHALENDRA; KUMAR, SANJAY (The Indian Journal of Animal Sciences, 2016)
An experiment was conducted to evaluate the effect of feeding wheat or rice based complete ration as mash or block form on feed intake, nutrient utilization, blood biochemicals and growth in growing crossbred female calves. Wheat and rice straw based complete feeds having different proportion of roughages in mash form were densified into blocks by applying the pressure of 3,000 psi for dwell time of 30 sec in the complete feed block making machine. Physical characteristics like weight, dimension, bulk density, post compression expansion and durability were evaluated. The highest bulk density (562.2 kg/m3) and the lowest post compression expansion (28.18%) was observed in rice straw (50% inclusion level) based complete feed block. The blocks were denser and durable without any change in nutritional composition, however, rice straw based feed blocks were more durable with less post compression expansion as compared to wheat straw based blocks. Crossbred female calves (24) of 10–12 months age were divided into 4 groups of 6 calves each on the basis of body weight. Calves were fed mash form of 50% wheat (WM50) or rice (RM50) straw whereas corresponding other group was offered compressed complete feed blocks of wheat (WB50) or rice (RB50) straw based diet ad lib. and 2 kg green oat. Feeding trial lasted for 90 days. A digestion trial of 7 days duration was conducted to assess nutrient utilization and blood samples of animals were collected on 85th day of the experimental feeding to anlayse blood bio-chemicals. Average daily weight gain and feed conversion efficiency did not differ in crossbred calves of different groups, however, body weight gain and feed intake was higher in calves fed block as compared to mash form of feed. The digestibility of DM, CP, EE and NFE did not differ among the groups. The blood glucose, total protein, albumin and globulin concentrations, and AST and ALT activities were similar among different groups. It is concluded that feeding of complete ration in block form is beneficial in terms of feed intake, nutrient utilization, growth and feed conversion efficiency in growing crossbred female calves.